Pediatric Kidney Disease : a case-based approach - Assadi, Farahnak (Philadelphia, Pa. : Elsevier, 2025)
The primary purpose of writing Pediatric Kidney Disease: A Case-Based Approach is to provide complete state-of-the-art reviews and assessments of kidney diseases in children that are frequently encountered in real-world routine daily clinical practice. More than 400 cases are divided into nine chapters consisting of acute and chronic kidney failures, congenital anomalies of the kidney and urinary tract, fluid, electrolytes and acid-base disorders, genetic disorders, glomerulonephritis, hypertension, tubulointerstitial diseases, and urinary tract infections. Each chapter contains extensive discussions of clinical characteristics, differential diagnosis, and treatments of relevant kidney disease. The book is ideal for residents and fellows rotating on nephrology services. The material is also useful as a first-line resource for other practicing physicians who need quick access to current scientific and clinical information on managing pediatric kidney disease.
Obsahuje QR kód s prístupom k rozširujúcim materiálom
Obsahuje bibliografie a register
Keywords: pediatria; choroby urologické; choroby a abnormality novorodenecké, vrodené a dedičné; rany a poranenia; choroby obličiek; poruchy acidobázickej rovnováhy; nefritída intersticiálna; hypertenzia renálna; glomerulonefritída; infekcie močového systému; dieťa; kazuistiky; monografia; kazuistiky